Commercial Education:: Colégio Comercial Visconde de Cairu, São Paulo/SP (1954-2002) - Garutti, Alessandra Maria Martins Gaidargi (Revista Labor, 2022)
The main theme of this paper is the history of the school institution Colégio Comercial Visconde de Cairu in the historical section from 1954 to 2002 - which corresponds to its period of operation. Established in the city of São Paulo, in the neighborhood of Belenzinho, this educational institution went through several phases of Brazilian educational history and a series of legislative changes, with a marked trajectory in the evolutionary process of commercial education in Brazil. Proposed from the framework of investigative Marxist dialectics, the history of the institution presented here proposes to study the whole based on particularities, illustrating changes in education history and their influence in the development of high school to the present days.